PELABELAN TOTAL TRIMAGIC SISI TERURUT TITIK-a PADA BEBERAPA GRAF - Aprilia, Maita; Soelistyo Utomo, Robertus Heri; Farikhin, Farikhin (MATEMATIKA, 2017)
Given graph G with number of vertex p and number of edge q. In this paper, we discussed a-vertex consecutive edge trimagic total labeling for several graphs which contain Bistar and Cycle Graph.